Implementasi Pendidikan Holistik Integratif Pada Anak Usia Dini di Kabupaten Bone - Iting, Andi (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
This study discusses the implementation of integrative holistic education in early childhood at Aisyiyah Bustanul Athfal Massalewangeng Kindergarten, Tanete Riattang Barat District, Bone Regency. The objectives of this study were (a) to determine the implementation of integrative holistic education in early childhood, (b) to describe the factors that become obstacles to the implementation of integrative holistic education in early childhood, and (c) to determine the efforts made to overcome obstacles to the implementation of integrative holistic education in early childhood at Aisyiyah Bustanul Athfal Massalewangeng Kindergarten, Tanete Riattang Barat District, Bone Regency. To obtain data in this study, the researcher used a qualitative research method, with descriptive analysis. Data collection techniques used in this study were observation, interviews, and documentation. Based on the results of the study, it was concluded that (a) the implementation of Integrative Holistic Education in Early Childhood at Aisyiyah Bustanul Athfal Massalewangeng Kindergarten, Tanete Riattang Barat District, Bone Regency is to provide comprehensive services, provide guidance for guardians; and implement learning oriented towards children's basic needs. (b) The factors that become obstacles to the implementation of holistic integrative education for early childhood in Aisyiyah Bustanul Athfal Massalewangeng Kindergarten, Tanete Riattang Barat District, Bone Regency are the lack of coordination with related elements in the community. The lack of response from guardians to coaching activities, and the lack of socialization, mentoring and evaluation from the government related to holistic integrative education, (c) efforts made to overcome obstacles to the implementation of holistic integrative education for early childhood in Aisyiyah Bustanul Athfal Massalewangeng Kindergarten, Tanete Riattang Barat District, Bone Regency are to coordinate with Posyandu and BKB (Bina Keluarga Balita), rebuild cooperation with guardians of students, and strive for the availability of data and information on the development of students as a whole